Konsep Panca Sradha Pada Lontar Putru Pasaji - Ida Bagus Putu Eka Suadnyana; I Nyoman Miarta Putra (Purwadita : Jurnal Agama dan Budaya, 2021)
Hindus not only believe in the embodiment of the One God, but also believe in God as an intangible essence (Nirguna Brahman). Hinduism has always been a source of inspiration that has inspired a number of traditional texts owned by people in Bali, one of which is Lontar Putru Pasaji. Lontar Putru Pasaji is a script inherited by Balinese people today. In Lontar Putru Pasaji contains noble educational values that should be emulated by all circles of society in behaving in everyday life. In addition, Lontar Putru Pasaji contains philosophical teachings on how humans can be free from Papa and can achieve heavenly happiness through the implementation of the Pitra Yadnya ceremony by paying attention to fish, meat or animals that can be used as serving materials for offerings to the Pitara, and which are not appropriate as offerings. The theory used to solve the research problem is Religious Theory to solve the teaching problems contained in Lontar Putru Pasaji. This research is in the form of a qualitative design. Data were collected using text study techniques and interview techniques. After the data was collected, the data were analyzed using descriptive data analysis techniques. Based on this analysis, the conclusions obtained as a result of the study are as follows: (1). The structure of Lontar Putru Pasaji consists of form, content, characterizations or characters, plot, theme and mandate. (2). The teachings contained in the Lontar Putru Pasaji are: (a). The Panca Sradha teachings consist of Widhi Sradha, Atma Sradha, Karmaphala Sradha, Punarbhawa Sradha, and Moksa Sradha.